2010
DOI: 10.1159/000319762
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rate and Clinical Pattern of Prostate Cancer in Kuwait: A Single-Center Experience

Abstract: Objective: To determine the detection rate and clinical pattern of prostate cancer in Kuwait. Subjects and Methods: One hundred and fifty-three males suspected of having prostate cancer based on elevation of prostate-specific antigen (PSA) of more than 4 ng/ml underwent transrectal-ultrasound (TRUS)-guided needle biopsy of the prostate between January 2003 and January 2008; these formed the study group. Analysis of prostate cancer was based on age, prostate volume, PSA level and on finding any abnormality base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…The cancer detection rate in this study increases with increase in the PSA levels [ Table 2 ]. This finding is in tandem with the findings of Jia et al [ 15 ] in China and Narayanaswamy[ 22 ] et al in the Middle East. The cancer detection rate of 25.0% at PSA range of 4.0–10.0 ng/ml in this study, was consistent with other studies from the Western world and the Eastern hemisphere as well as similar studies from our locality.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The cancer detection rate in this study increases with increase in the PSA levels [ Table 2 ]. This finding is in tandem with the findings of Jia et al [ 15 ] in China and Narayanaswamy[ 22 ] et al in the Middle East. The cancer detection rate of 25.0% at PSA range of 4.0–10.0 ng/ml in this study, was consistent with other studies from the Western world and the Eastern hemisphere as well as similar studies from our locality.…”
Section: Discussionsupporting
confidence: 90%
“…[ 15 ] The prostate cancer detection rate increased proportionately with increase in prostate volume [ Table 3 ]. This observation is at variance with that of Narayanaswamy et al [ 22 ] who reported a decreased detection rate with increasing prostate volume with the majority of the cancer patients having the prostate volume of <50.0 g.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In our study we have further strati ed the grey zone levels into 4 categories and analysed each category statistically.Many studies from other countries all over Asia have reported wide variations in the TRUS biopsy yield. large retrospective study from China by Na R et al, reported lower yield for patients with serum PSA less than 10 ng/mL and (10-20) ng/mL despite overall high yield11 . Two studies from Singapore by Lee et al, and Teo et al, con rmed the lower yield for serum PSA below 10 ng/mL which was less than 21%12,13 .…”
mentioning
confidence: 99%